Pengaruh Influencer Sosial Media Terhadap Toleransi Beragama di Kalangan Gen Z - Abidin, Muhammad Mukhlish (Mafa Press, 2026)
This study aims to analyze the influence of social media influencers on the formation of tolerance among Generation Z. The increasing role of influencers in shaping public opinion, including on religious issues, makes this research relevant in the context of religious moderation in the digital era. This study used a qualitative descriptive approach, collecting data through in-depth interviews with 10 informants born in the 2000s who actively use social media. The results indicate that influencers have both positive and negative influences on religious tolerance among Generation Z. Moderate influencers, through their use of humanistic, educational, and dialogical narratives, foster openness, inclusiveness, and respect for differences among their followers. Conversely, provocative influencers, through their emotional, confrontational, and exclusive content, actually reinforce the polarization of religious identities. However, the greatest influence is determined by the digital maturity of the audience and the ability of Generation Z social media users to critically analyze information.